Peran Perempuan Pedesaan dalam Menopang Usaha Kerupuk Kemplang: Studi Kasus di Sumatera Selatan: Role of Rural Women in Sustaining the Fish Crackers Business: A Case Study in South Sumatra - Yunindyawati Yunindyawati (Society, 2023)
The rural woman is a valuable human resource, especially in fulfilling the economic functions of the family and the home alongside males. In rural families, women perform not only a reproductive but also a productive and social role. This research is original because it examines the contribution of women in rural areas, particularly in villages with local potentials, such as river and swamp fish. Women transform fish into crackers, which they sell to increase the family’s income. This study examines rural women’s contribution to the fish crackers business. The qualitative research was conducted in Tebing Gerinting Village, South Indralaya Sub-district, Ogan Ilir Regency, South Sumatra. Data collection technique involving in-depth interviews with the informant. Using qualitative analysis methods, the collected data were analyzed. Women perform a variety of roles in the production of crackers fish, including dough preparation, crackers fish formation, boiling, drying/drying process, roasting, packaging, and sales. Fish crackers are a commercially produced item that incorporates the contributions of women. Women in the manufacturing crackers fish business have difficulty finding laborers. There is no business capital because the raw materials for making fish crackers are supplied by fixed-supply agents. The agents of the fish were from Palembang, while the agents of tapioca flour were from Lampung. All family members are involved in the marketing of fish crackers. They sold to the market in Tanjung Raja, Indralaya, and even to outside areas such as Pendopo, Kayuagung, Komering, Sungai Pinang, Ketapang, Tanjung Enim, Lahat, Prabumulih, Palembang and up to outside the cities, such as Lampung. Additionally, they sell fish crackers on the road next to their home. The contribution of women to economically productive activities can ensure the survival and growth of venture fish crackers. It can increase their family’s nutritional security.